(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Dendrimers are synthetic, highly branched, monodisperse macromolecules of nanometer dimensions with exact and large number of functional groups, distributed with unprecedented control, makes them a promising scaffolds, for drug delivery. Dendrimers serves as an ideal vehicle for cancer therapy, immunology, vaccines, antivirals, biosensors for diagnostics, neuron capture therapy, photodynamic therapy and photo thermal therapy. Dendrimers chemistry is one of the most fascinating and rapidly expanding areas in the field of chemistry. Prior to the dendrimer technology, nanoparticle drug delivery systems were one of the choicest systems owing to their selectivity and stability of therapeutic agents incorporated into the system. However, few drawbacks such as reticuloendothelial system (RES) uptake, drug leakage, immunogenicity, hemolytic toxicity, cytotoxicity, hydrophobicity etc., impede the usage of these nanostructures. Further, these shortcomings shall be circumvented by modifying the surface engineering, such as poly ester dendrimer, arginine dendrimer, glycol dendrimer, PEGylated dendrimers etc., Unique properties of uniform size, water solubility, modifiable surface functionality and availability of internal cavities makes them intriguing carrier for biological and drug delivery system. In the present review, we focused on the bioactive agents that can be easily encapsulated into the interior cavity (or) chemical attachment, conjugation (or) physically adsorbed on to the dendrimer surface to serve the desired properties of the carrier to cater specific needs of the active components, its characterization and application.